THE MYTH OF THE SOUTH AS A COUNTERPOINT TO THE OPPOSITION OF EAST – WEST AND A BASIS OF THE MYTH OF CENTRAL EUROPE - Wierzejska, Jagoda (Porównania, 2012)
The article aims at considering Central Europe and appreciating it in connection with the category of the South. This means the change from the horizontal, parallel paradigm, which imposes the necessity of defining Central Europe by reference to the East and West, to the vertical, meridian paradigm, enabling the creation of the myth of Central Europe, where the main reference point are the Balkan nations. A look at the South as a counterpoint to the opposition East – West has its antecedents in the 30s of the 20th century. In the Polish prose created after 1989, especially in the works of Andrzej Stasiuk, it is possible to specify the elements of the myth of the South as the basis of the myth of Central Europe, such as: themes of Austria-Hungary, the idea of civilization of the Danube, the creation of the Gypsies as cultural heroes and the specifically transformed topos of the “poetry of ruins”.